Pan-selectin inhibitors as potential therapeutics for COVID-19 treatment: in silico screening study - Šmak, Pavel; Chandrabose, Selvaraj; Tvaroška, Igor; Koča, Jaroslav (Glycobiology, 2021)
Coronavirus disease 2019 (COVID-19) has spread rapidly throughout the globe. The spectrum of disease is broad but among hospitalized patients with COVID-19, respiratory failure from acute respiratory distress syndrome is the leading cause of mortality. There is an urgent need for an effective treatment. The current focus has been developing novel therapeutics, including antivirals, protease inhibitors, vaccines and targeting the overactive cytokine response with anti-cytokine therapy. The overproduction of early response proinflammatory cytokines results in what has been described as a "cytokine storm" is leading eventually to death when the cells fail to terminate the inflammatory response. Accumulating evidence shows that inflammatory cytokines induce selectin ligands that play a crucial role in the pathogenesis of inflammatory diseases by mediating leukocyte migration from the blood into the tissue. Thus, the selectins and selectin ligands represent a promising therapeutic target for the treatment of COVID-19. In this paper, potential pan-selectin inhibitors were identified employing a virtual screening using a docking procedure. For this purpose, the Asinex and ZINC databases of ligands, including approved drugs, biogenic compounds and glycomimetics, altogether 923,602 compounds, were screened against the P-, L- and E-selectin. At first, the experimentally confirmed inhibitors were docked into all three selectins' carbohydrate recognition domains to assess the suitability of the screening procedure. Finally, based on the evaluation of ligands binding, we propose 10 purchasable pan-selectin inhibitors to develop COVID-19 therapeutics.
Keywords: virtual screening; Antiviral Agents; SARS-CoV-2; selektiny; Databases, Chemical; antivirové látky; počítačová simulace; pan-selectin inhibitors; farmakoterapie COVID-19; lidé; COVID-19; Drug Evaluation, Preclinical; Computer Simulation; selectins; Selectins; preklinické hodnocení léčiv; biomimetické materiály; Biomimetic Materials; COVID-19 Drug Treatment; docking; chemické databáze; Humans